Hubungan Antara Kesadaran Privasi dan Perilaku Aman Mahasiswa di Media Sosial - Harry Zulkifli (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
The development of social media has encouraged students to be more active in interacting, sharing information, and establishing relationships online. However, the high intensity of social media use also increases the risk of personal data leakage. This literature study aims to examine the relationship between privacy awareness and students' safe behavior in social media use. The research was conducted by examining various sources, including scientific journals, articles, research reports, books, and online references relevant to digital security issues. The results of the study show that privacy awareness has a significant role in shaping students' safe behavior. This awareness is reflected through the practice of using strong passwords, the implementation of two-factor authentication, and prudence in sharing personal information in the digital space. Although knowledge about digital threats is quite adequate, students' safe behavior is still influenced by the level of internalization of privacy awareness. Therefore, increasing privacy awareness requires not only information, but also educational strategies that emphasize the formation of consistent digital attitudes and habits. This study makes an important contribution to understanding the relationship between privacy awareness and safe behavior, as well as being the basis for the development of more effective digital literacy programs among students.